Histamine signaling and metabolism identify potential biomarkers and therapies for lymphangioleiomyomatosis. Issue 9 (11th August 2021) - Herranz, Carmen; Mateo, Francesca; Baiges, Alexandra; Ruiz de Garibay, Gorka; Junza, Alexandra; Johnson, Simon R; Miller, Suzanne; García, Nadia; Capellades, Jordi; Gómez, Antonio; Vidal, August; Palomero, Luis; et al.
Abstract: Inhibition of mTOR is the standard of care for lymphangioleiomyomatosis (LAM). However, this therapy has variable tolerability and some patients show progressive decline of lung function despite treatment. LAM diagnosis and monitoring can also be challenging due to the heterogeneity of symptoms and insufficiency of non‐invasive tests. Here, we propose monoamine‐derived biomarkers that provide preclinical evidence for novel therapeutic approaches. The major histamine‐derived metabolite methylimidazoleacetic acid (MIAA) is relatively more abundant in LAM plasma, and MIAA values are independent of VEGF‐D. Higher levels of histamine are associated with poorer lung function and greater disease burden. Molecular and cellular analyses, and metabolic profiling confirmed active histamine signaling and metabolism. LAM tumorigenesis is reduced using approved drugs targeting monoamine oxidases A/B (clorgyline and rasagiline) or histamine H1 receptor (loratadine), and loratadine synergizes with rapamycin. Depletion of Maoa or Hrh1 expression, and administration of an L‐histidine analog, or a low L‐histidine diet, also reduce LAM tumorigenesis. These findings extend our knowledge of LAM biology and suggest possible ways of improving disease management. Synopsis: In this study, lymphangioleiomyomatosis (LAM) is characterized by active histamine metabolism and signaling, which opens new opportunities for advancing disease monitoring and/or treatment. LAM cells have enhanced metabolism of histamine and the major metabolite product is found to be overabundant in blood plasma of patients. Histamine plasma levels are associated with disease features and status. LAM cells are responsive to histamine signaling through H1 histamine receptor. Targeted inhibition of histamine metabolism or signaling hinders LAM disease in a preclinical model. The anti‐histamine loratadine effect on LAM may be synergistic with the standard of care, rapamycin (sirolimus). Abstract : In this study, lymphangioleiomyomatosis (LAM) is characterized by active histamine metabolism and signaling, which opens new opportunities for advancing disease monitoring and/or treatment.